2012
DOI: 10.1002/pros.22488
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative RT‐PCR analysis of PSA and prostate‐specific membrane antigen mRNA to detect circulating tumor cells improves recurrence‐free survival nomogram prediction after radical prostatectomy

Abstract: Data from modern quantitative RT-PCR to detect circulating prostate-derived PSA and PSM mRNA pre- and post-RP improves the accuracy of the Kattan nomogram to predict biochemical recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Besides, qRT-PCR targeting the PSMA transcript was applied to identify CTCs in patients before and after radical prostatectomy [15]. However, to our best knowledge, this is the first study implementing PSMA staining in the FDA-cleared CellSearch ® system that offers the possibility to capture CTCs in a standardized and highly reproducible manner within the clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, qRT-PCR targeting the PSMA transcript was applied to identify CTCs in patients before and after radical prostatectomy [15]. However, to our best knowledge, this is the first study implementing PSMA staining in the FDA-cleared CellSearch ® system that offers the possibility to capture CTCs in a standardized and highly reproducible manner within the clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the mRNA encoding PSA has been the most extensively studied in clinical trials (63,69,72). Mohamadi et al (73) developed a velocity valley chip to efficiently capture magnetic nanoparticle-bound CTCs.…”
Section: Enrichment and Detection Strategies For Ctcmentioning
confidence: 99%
“…The approach was successfully validated using samples collected from patients with PCa: CTCs and PSA mRNA sequences were detected in all cancer patient samples and not in the healthy controls. In addition, quantitative RT-PCR analysis of PSA and PSMA mRNA to detect circulating tumor cells improves recurrence-free survival nomogram prediction following radical prostatectomy (72). Furthermore, androgen receptor (AR), kallikrein-related peptidase (KLK)2, KLK3, PCa antigen 3 (PCA3), transmembrane protease serine 2 and ETS-related fusion gene (TMPRSS2-ERG), AR splice variant 7 messenger RNA (AR-V7) and prostate stem cell antigen mRNA are also utilized to identify PCTCs (63,69,7476).…”
Section: Enrichment and Detection Strategies For Ctcmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, PSA mRNA copy number used as a surrogate for CTC count was predictive of recurrence after radical prostatectomy (Yates et al, 2012). Several studies have shown significant differences in PSA and PSMA mRNA copy number among patients with benign prostatic hypertrophy, localized prostate cancer, and metastatic disease (Zhang et al, 2008; Kalfazade et al, 2009).…”
Section: Ctc Detection Methodsmentioning
confidence: 99%